Asymmetric Price Transmission of Some Basic Commodities in Indonesia - Mahjus Ekananda (Media Ekonomi dan Manajemen, 2023)
The prices of these international goods, world oil prices, exchange rates, and government policies, always influence developments in the current global era that drive domestic commodity prices. This study aims to analyze the effect of asymmetric price transmission on several Indonesian domestic commodities. Asymmetric price transmission occurs if the speed of price adjustment above or below the price trend is not the same. Positive or negative price changes occur if the price is above or below the price trend. Under dynamic conditions, each price will adjust to the long-term price level. This study applies the error correction model (ECM) method to capture the speed of adjustment of each commodity following the long-term price level. This study involves asymmetric price transmission to see price adjustments. Econometric testing through the error correction model is used to determine how much the domestic price adjustments are when there is an increase or decrease in international prices for essential commodities. The results showed an adjustment in domestic prices when global prices increased or decreased for wheat flour, granulated sugar, soybeans, beef, and broiler meat. Based on the coefficient and significance level, there was no domestic price adjustment for rice and broiler chicken eggs. Policy implications include providing input for policymakers in determining prices so that market prices are stable and in line with people's purchasing power.